PENGARUH KESULITAN BELAJAR MENGOLAH MAKANAN KONTINENTAL TERHADAP PRESTASI BELAJAR PADA SISWA SMK - Dwi Ariyani (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2017)
This study aimed to know the description of learning difficulties of cooking continental foods and learning achievement and to know the influence of learning difficulties of cooking continental foods and learning achievement of continental food management subject. The type of the study was ex-post facto. Data collection methods used questionnaires and documentation. Data analysis methods used a qualitative analysis and hypothesis testing by using correlation product moment that was started by normality and linearity test.Â Based on the result of hypothesis analysis, the score of robs was 0.603 > 0.235. It could be stated there was a negative influence of learning difficulties of cooking continental foods and learning achievement of continental food management subject. it means that the higher difficulty, so the lower learning achievement of continental food management subject. This study shows that learning difficulties of cooking continental foods was in enough category with the percentage 72.46% and learning achievement was in enough category with the percentage 78.26%. The determinant coefficient (R2) was 0.364, it means that parentsâ€™ income gave contribution for about 36.4%. Key words: learning difficulties, learning achievement